IMPLEMENTASI SISTEM MONITORING DAYA LISTRIK REAL-TIME BERBASIS IOT UNTUK MENINGKATKAN EFISIENSI ENERGI PADA MESIN PRES - NILA AFIKA (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Electrical energy consumption in Micro, Small, and Medium Enterprises (MSMEs) is often monitored manually, leading to potential energy waste, inefficient power utilization, and the risk of overload that may damage electrical equipment. This issue is also found at Carica Ni'mat MSME in Dieng, particularly in the heat sealing equipment that is intensively used during the production process. This study aims to design an Internet of Things (IoT)-based electrical power monitoring system capable of monitoring electrical parameters, including voltage, current, power, and electrical energy (kWh), in real time. The research method consists of requirements identification, literature review, field observation, system design, prototype development, and performance testing using a PZEM-004T sensor, ESP32 microcontroller, 20×4 LCD, LED, and buzzer as a warning system. The proposed system is expected to accurately display energy consumption data, provide notifications when an overload occurs, and support continuous energy usage recording. The results of this system design are expected to improve the efficiency of electrical energy management, enhance the operational safety of equipment, and provide a modern, practical, and easily implementable power monitoring solution for MSMEs.